Physicochemical characterization of spray dried cefixime polymeric nanoparticles using factorial design approach - Pooja Satish Desai, Yogesh Vilas Pore (Journal of Applied Pharmaceutical Science, 2016)
The objective of the present study was to improve the physicochemical properties of poorly water soluble cefixime by preparing its nanoparticles using a hydrophilic polymer polyvinylpyrrolidone K30 (PVP). The nanoparticles of cefixime were prepared by spray drying technique. A 32 factorial design approach was employed for the optimization of nanoparticle batches. The present model demonstrated significance of factors such as drug to polymer ratio (X1) and feed flow rate (X2) of spray dryer on the production yield (Y1), particle size (Y2) and % drug release at 15 min (Y3). The pure drug and prepared nanoparticles were characterized by Fourier transformation infrared spectroscopy (FTIR), Differential scanning calorimetry (DSC), X-ray powder diffraction (XPRD), Scanning electron microscopy (SEM), particle size, saturation solubility and in vitro drug release. The results of DSC and XPRD revealed transformation of the crystalline nature of cefixime into an amorphous form which was supported by SEM. A significant improvement in solubility and dissolution rate was noticed in case of prepared nanoparticles as compared to pure cefixime. These results suggested that preparation of polymeric nanoparticles by spray drying technique might be a promising approach for improving the physicochemical properties of cefixime.
Keywords: Cefixime,factorial design,spray drying, nanoparticles, polymeric, physicochemical characterization.